Development of ortho-phthalic polyester-based composites with glass waste for electrical sector applications - da Silva, Wladmir Teodoro; de Oliveira, Jhonatan Bispo; Salles Neto, Paulo; Ferreira, Venilton Menezes Vieira; de Oliveira Buzatti, Renata Santiago; de Cassia Oliveira Sebastião, Rita; Pedroso, Emerson Fernandes; de Oliveira, Ângelo Rocha; de Souza, Patterson Patricio; de Oliveira Patricio, Patrícia Santiago (Cleaner Engineering and Technology, 2025)
Using waste materials in polymer composites has gained attention for its ecological benefits and material properties. This work investigates the production of composites using waste glass powder and Ortho-phthalic polyester resin. Before cure processing, the glass powder was added to the polymer matrix at a 50 wt% ratio. Characterization techniques included scanning electron microscopy (SEM), contact angle measurement, thermogravimetric analysis (TG), Fourier transform infrared spectroscopy (FTIR), and tensile tests. Flammability tests revealed that the compounds exhibit flame-retardant behavior. The composites exhibited improved mechanical properties compared to pure resins, with increased compressive strength (3–15 %), impact strength (9–16 %), and a higher tensile modulus (2.5 times). The results show that glass can reinforce polymers while maintaining hydrophobic properties. The composite conductivity with glass waste was reduced by almost 95 % compared to pure resin. These findings suggest that glass-reinforced polymers can be effectively used in electrical applications as insulators, protective mechanisms, or carriers in electrical circuits. [Display omitted] •Use of waste glass powder as a reinforcing filler in polyester•The glass waste acted as a flame retardant for the resin•Waste glass lowers conductivity, making it suitable for electrical applications.